Implementasi Prinsip-Prinsip Good Governance dalam Memajukan Kabupaten Jember - Moh Anwar Nuris (Sharia Faculty, Kiai Haji Achmad Siddiq State Islamic University of Jember, 2020)
In realizing good governance in government, we need a foundation to make it happened. Good governance is the basis for the value of government administration which is oriented towards restoring the community's dignity in order to rebuild the image of the government as a just servant. This was accompanied by the increasing demands for democracy, recognition of human rights, which resulted in demands for management characterized by good governance. The results show that: (1) The application of the principles of good governance in the Jember Regency Government is still insufficient because of the many violations committed by the government (2) the process of applying the principles of good governance in advancing Jember Regency is still lacking due to the many violations committed by the government. Jember Regency Government in carrying out alleged violations of statutory regulations. Starting from the management of the State Civil Apparatus (ASN), the use of government apparatus authority, and the management of regional finances which have a massive impact on ASN and the community so that the impeachment of the Regent of Jember by the Regional House of Representatives (DPRD Jember) affects the implementation of government in Jember Regency so that it has an impact on the performance of the Regent of Jember. (3). Factors that hinder the preparation of the RAPBD in implementing the principles of good governance in Jember Regency.